LINGUISTIC MINIMALISM AND ETHICAL AMBIGUITY: A CORPUS- ASSISTED STYLISTIC ANALYSIS OF NARRATIVE VOICE IN SELECTED NOVELS OF J. M. COETZEE - S. KUMARAN ARUL DEVARAM; Dr.S. GUNASEKARAN (The Bioscan, 2026)
This study investigates linguistic minimalism and its relationship to ethical ambiguity in selected novels of J. M. Coetzee through a corpus-assisted stylistic framework. While existing scholarship has largely examined Coetzee’s fiction from political, postcolonial, and philosophical perspectives, limited attention has been paid to the systematic linguistic patterns that shape his distinctive narrative voice. Addressing this gap, the present research combines quantitative corpus tools with qualitative close reading to examine lexical density, sentence length distribution, modality, passive constructions, and patterns of speech representation in Waiting for the Barbarians, Life & Times of Michael K, and Disgrace.